Cambridge handbook of engineering education research - Johri, Aditya, 1976-; Olds, Barbara M. (Cambridge : Cambridge University Press, 2014)
'The Cambridge Handbook of Engineering Education Research is the critical reference source for the growing field of engineering education research, featuring the work of world luminaries writing to define and inform this emerging field. Since a landmark issue of the Journal of Engineering Education in 2005, in which senior scholars argued for a stronger theoretical and empirically driven agenda, engineering education has quickly emerged as a research-driven field with an increasing quality and quantity of both theoretical and empirical work that draws on many social science disciplines, disciplinary engineering knowledge, and computing. The Handbook draws extensively on contemporary research in the learning sciences, examining how technology affects learners and learning environments, and the role of social context in learning. The Handbook is organized into six parts and thirty-seven chapters based on the research agenda from a series of interdisciplinary colloquia funded by the US National Science Foundation and published in the Journal of Engineering Education in October 2006'--
'This volume reflects the richness and comprehensiveness of the emerging field of EER and will be of tremendous utility to students as well as those seeking an introductory overview. The editors have carefully selected authors who are leading, globally-recognized scholars writing in their areas of expertise. This volume comes at a particularly opportune time as the broad engineering education community seeks to better define the required elements of a 21st Century engineering education in an increasingly integrated global community where the solutions to a growing array of social, political, and economic challenges require access to engineering knowledge. The traditional image of the solitary engineer is no longer valid. Successful engineering research, innovation and practice require collaboration with and integration of professionals from other fields. The engineering education system faces stresses from larger changes within education systems overall, especially political pressures to reduce costs, and stresses on engineering faculty to be increasingly effective in teaching, research, and service. There is a tremendous need for a robust research base to inform future practice in this unfamiliar environment. This volume serves as an important tool for accomplishing this goal'--
Machine generated contents note: Foreword; Introduction; 1. Chronological and ontological development of engineering education as a field of scientific inquiry Jeff Froyd and Jack Lohmann; 2. Learning theories for engineering education practice and research Wendy Newstetter and Marilla Svinicki; 3. Situative framework for engineering learning research Aditya Johri, Barabara M. Olds and Kevin O'Connor; 4. The social nature of representational engineering knowledge Wolff-Michael Roth; 5. Conceptual change and misconceptions in engineering education: curricular-, measurement-, and theoretically focused approaches Ruth Streveler, Shane Brown, Geoffrey Herman and Devlin Monfort; 6. Engineers as problem solvers David Jonassen; 7. Professional engineering work R. Stevens, Aditya Johri and Kevin O'Connor; 8. Problem-based and project-based learning in EE - merging models Anette Kolmos and Eric DeGraaff; 9. Case studies in engineering Claire Davis and Aman Yadav; 10. Curriculum design in the middle years Susan Lord and John Chen; 11. Engineering design education Cindy Atman, Jim Borgford-Parnell, Janet McDonnell, Ozgur Eris and Monica Cardella; 12. Adaptive expertise and knowledge fluency in design and innovation Ann McKenna; 13. Learning disciplinary ideas and practices through engineering design Janet Kolodner and Kristen Wendell; 14. Engineering identity Karen Tonso; 15. Studying the career pathways of engineers: an illustration with two datasets Sheri Sheppard, Shannon Gilmartin, Samantha Brunhaver and Anthony Antonio; 16. Retention and persistence in engineering education Gary Lichtenstein, Helen Chen, Karl Smith and Theresa Maldonado; 17. Social justice and inclusion: women and minorities in engineering Donna Riley, Amy Slayton and Alice Pawley; 18. Community engagement in engineering education as a way to increase inclusiveness Chris Swan, Kurt Paterson and Angela Bielefeldt; 19. Translating research to widespread practice in engineering education Tom Litzinger and Lisa Lattuca; 20. Research-guided teaching practices: engineering threshold concepts as an approach to curriculum renewal Caroline Baillie and Sally Male; 21. Engineering instruction development: programs, best practices, and recommendations Rich Felder, Rebecca Brent and Michael Prince; 22. Understanding disciplinary cultures: the first step to cultural change Elizabeth Godfrey; 23. Preparing engineering educators for engineering education research Maura Borrego and Ruth Streveler; 24. Studying teaching and learning in undergraduate engineering programs: conceptual frameworks to guide research on practice Lisa Lattuca and Tom Litzinger; 25. Design-based research in engineering education: current steps and next steps A. Kelly; 26. Quantitative and mixed-methods research: approaches and limitations Barbara Moskal and Teri Reed-Rhoades; 27. Framing qualitative methods in engineering education research: established and emerging methodologies Jenni Case and Greg Light; 28. Conducting interpretive research in engineering education Aditya Johri; 29. The science and design of assessment in engineering education Jim Pellegrino, L. V. DiBello and Sean Brophy; 30. Engineering communication M. Paretti, L. McNair and J. Leydens; 31. Use of technology in engineering education K. Madhavan and E. Lindsay; 32. Global and international issues in engineering education A. Johri and B. Jesiek; 33. Engineering ethics B. Barry and J. Herkert; 34. The normative contents of engineering formation: engineering studies G. Downey; 35. Interdisciplinarity in engineering practice N. Nerssesian and W. Newstetter; Conclusion.
Includes bibliographical references and index.
Keywords: Engineering -- Study and teaching -- Handbooks, manuals, etc